2008
DOI: 10.1124/jpet.108.145128
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Anti-Vascular Endothelial Growth Factor (VEGF) Antibody Reduces Severity of Experimental Ulcerative Colitis in Rats: Direct Evidence for the Pathogenic Role of VEGF

Abstract: In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 40 publications
4
63
0
Order By: Relevance
“…In rats, anti-VEGF antibody was investigated in colitis induced by iodoacetamide given intracolonically, and the results showed markedly less severe colitis as well as significant reductions in pro-inflammatory cytokines compared with controls. The beneficial effect of anti-VEGF antibody on colitis may be due to its moderating effects on vascular permeability and inflammatory cell recruitment [319]. Further studies showed that the levels of VEGF-A and VEGFR-2 were increased in patients with IBD as well as in DSS-treated mice.…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 93%
“…In rats, anti-VEGF antibody was investigated in colitis induced by iodoacetamide given intracolonically, and the results showed markedly less severe colitis as well as significant reductions in pro-inflammatory cytokines compared with controls. The beneficial effect of anti-VEGF antibody on colitis may be due to its moderating effects on vascular permeability and inflammatory cell recruitment [319]. Further studies showed that the levels of VEGF-A and VEGFR-2 were increased in patients with IBD as well as in DSS-treated mice.…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 93%
“…Increased VEGF levels during early stages of UC may provide a mechanistic clue to impaired endothelial barrier and increased VP. In our previous study, we demonstrated that neutralizing anti-VEGF antibody diminished colonic VP and improved clinical and morphologic signs of IA-UC, 15 thus providing further support for the pathogenic role of increased VP in UC.…”
Section: Endothelial Damage In Ulcerative Colitismentioning
confidence: 99%
“…Other and our laboratories demonstrated activation of VEGF in UC, especially in its early phase, especially that neutralization of endogenous VEGF with specific anti-VEGF antibody abolishes increased endothelial microvascular permeability and prevents development of experimental UC. 15 In addition to elevated VEGF, other non-VEGF mechanisms such as activation of TLR2 by oxidation stress can contribute to increased endothelial microvascular permeability in UC. 44 TLR2 are present on some endothelial cells and TLR2 agonist increases endothelial monolayer permeability in vitro.…”
Section: Endothelial Damage In Ulcerative Colitismentioning
confidence: 99%
See 1 more Smart Citation
“…It will be of interest, therefore, to determine in the IBD setting whether ID1-expressing cells derived from the bone marrow reach the inflamed colon and whether these cells are of functional consequence in response to tissue injury. Although anti-VEGF therapy has been reported to ameliorate experimental colitis in association with reducing excessive vascular permeability, 46 it may also have the Figure 7 Id1 deletion in endothelial cells sensitizes mice to more severe colitis. Mice were given plain drinking water or 2.5% dextran sulfate sodium (w/v) for 7 days, followed by 14 days of plain drinking water.…”
Section: Discussionmentioning
confidence: 99%